Bus stop design strategy based on visual comfort level in Bandung City - Kania, Nada Elfira Dwi; Hapsoro, Agustinus Nur Arief; Sudarisman, Irwan; Belasunda, Riksa (ARTEKS : Jurnal Teknik Arsitektur, 2024)
High sunlight and poor air quality in the city of Bandung affect the level of visual comfort. In designing bus stops, space is needed that has visual comfort so that the facilities are maintained and can function well. This research was conducted to determine visual comfort as measured using the Daylight Factor (DF) at bus stops in Bandung. The method used is a quantitative experiment using Drajmarsh and Ladybug software. To identify a bus stop design with stable visual comfort, analysis was conducted at various times and places. The results of the study are guidelines for creating publicly accessible spaces, such as bus stops, in Bandung that make utilization of natural light from the sun from morning to night. This light is crucial for visual information, thermal comfort, and building energy efficiency.